Bridging biodiversity and ecosystem services through useful plant species - Nina Obiar; Isaac Eckert; Janelle Baker; Daniel Moerman; Laura J. Pollock (Plants, People, Planet)
Social Impact Statement Global change endangers the terrestrial vegetation that sustains us. Therefore, policymakers need to make informed decisions about what and where to protect. However, with limited resources, we must decide whether to protect the intrinsic value of plants or their value to humans. Protecting both is possible. By investigating the distributions of over 3000 of Canada's useful native plants defined in ethnobotanical databases, we identified areas that are essential in harbouring plant benefits. Here, we bridge biodiversity with the benefits it provides to inform conservation policies by prioritizing plant species. Summary Plants are foundational for ecosystems and provide essential services to humans, but little is known about the distribution and protection about useful plants. Here, we address how well the biodiversity of all plants captures the diversity and conservation status of plants that provide human uses. We calculated diversity metrics for plants in Canada at 1‐km2 spatial scale based on species distribution models and a large plant‐use database for use categories of food and feed, medicinal, biochemical and genetic resources and materials. We used the Species Protection Index (SPI) to determine whether species are adequately represented in protected areas and derive a new index—Useful Species and Globally Endangered (USaGE)—to identify important species for conservation based on the combination of metrics of usefulness and (USa) metrics of extinction risk (GE) obtained from the Committee on the Status of Endangered Wildlife in Canada (COSEWIC) species assessments. Overall, c. 30% of native plants has documented uses, and plant richness is correlated with useful plant richness. Useful plants are generally concentrated in southern and agricultural areas, with the exception of some use categories (e.g., medicinal plants are also prevalent in coastal and boreal regions). Around 94% of useful species are inadequately represented in Canada's existing protected areas, including many important USaGE species like American Ginseng. Our combined approach identifies priority species and areas in need of conservation that have a long and extensively documented record of potentially providing ecosystem services to humanity.